ANALISIS KETERLAKSANAAN PEMBELAJARAN KURIKULUM MERDEKA DI KELAS IV SEKOLAH DASAR NEGERI 40 PONTIANAK UTARA - Melisa, Melisa -; Halidjah, Siti; Pranata, Rio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to describe the implementation of the Merdeka Curriculum in the fourth-grade class at State Elementary School 40 in North Pontianak. The background of this research stems from the 2022 curriculum change, where the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia introduced the Merdeka Curriculum as an effort to respond to the increasingly complex challenges in education. The Merdeka Curriculum is designed for more student-centered learning, aligned with their characteristics and needs, while reducing the administrative burden often faced by teachers. This research uses a qualitative method, focusing on understanding social issues based on real-life conditions in a holistic, complex, and detailed manner. The purpose of qualitative research is to gather data and information that cannot be processed using statistical methods. In the planning phase, the teacher already used the Merdeka Curriculum modules. The learning activities also focus on student involvement in the learning process, with the teacher providing engaging activities to motivate and enhance student learning. The assessment conducted by the teacher is formative. The school"™s facilities support the implementation of the Merdeka Curriculum, and the school fully supports teachers by offering guidance and training on the Merdeka Curriculum. Based on the research findings, it was concluded that the implementation of the Merdeka Curriculum in the fourth-grade class at State Elementary School 40 North Pontianak has been successful, with modules and learning activities aligned with the curriculum's requirements.